2012
DOI: 10.1007/s13204-012-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

A simple degradation method for sulfur mustard at ambient conditions using nickelphthalocyanine incorporated polypyrrole modified electrode

Abstract: Electrocatalytic degradation of sulfur mustard (SM) was studied using a gold electrode modified with nickelphthalocyanine and polypyrrole (NiPc/pPy/Au) in the presence of a cationic surfactant cetyltrimethyl ammonium bromide. Several techniques such as cyclic voltammetry, scanning electron microscopy, electrochemical impedance spectroscopy, energy dispersive X-ray spectroscopy and Raman spectroscopy have been employed for the characterization of modified electrodes. NiPc/pPy/Au modified electrode exhibited exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…where m is a parameter related to peak-to-peak separation, R, T, and F have their usual meanings (T = 291 K, n = 1, m = 0.05 V, v = 100 mV s À 1 ). k value is higher than those of 0.436 s À 1 for nickelphthalocyanine incorporated polypyrrole film [28], 1. [30].…”
Section: Electron Transfer Ability Of the Ptnps/poly (Py-co-appy)/urease Filmmentioning
confidence: 63%
See 1 more Smart Citation
“…where m is a parameter related to peak-to-peak separation, R, T, and F have their usual meanings (T = 291 K, n = 1, m = 0.05 V, v = 100 mV s À 1 ). k value is higher than those of 0.436 s À 1 for nickelphthalocyanine incorporated polypyrrole film [28], 1. [30].…”
Section: Electron Transfer Ability Of the Ptnps/poly (Py-co-appy)/urease Filmmentioning
confidence: 63%
“…where m is a parameter related to peak-to-peak separation, R, T, and F have their usual meanings (T = 291 K, n = 1, m = 0.05 V, v = 100 mV s À 1 ). k value is higher than those of 0.436 s À 1 for nickelphthalocyanine incorporated polypyrrole film [28], 1.3 s À 1 for hemoglobin and poly-pyrrole based nanocomposite [29], 1.71 s À 1 for hemoglobin modified polypyrrole/Co 3 O 4 film and 1.67 s À 1 glucose oxidase modified polypyrrole/Co 3 O 4 film [30]. This result confirmed the successful adsorption of PtNPs into the copolymer and revealed that PtNPs with strong conductivity could improve the electron transfer efficiency of the copolmeric film.…”
Section: Electron Transfer Ability Of the Ptnps/poly (Py-co-appy)/ure...mentioning
confidence: 65%
“…Therefore, the transition of crystalline packing from α to β-phase possibly results from the transfer energy from Bi dopants that has higher deposition temperature to NiPc matrix that requires lower temperature to evaporate. All hybrid films show similar peak positions at 593, 688, 1141, 1340 and 1551 cm -1 corresponding to the vibration of benzene ring deformation, macrocycle breathing, pyrrole ring breathing vibration, isoindole ring stretching and pyrrole ring stretching, respectively [13,14]. No change in raman spectrum of the hybrid films doped with Bi suggests that there is no chemical bond taken place between Bi and NiPc.…”
Section: Resultsmentioning
confidence: 95%
“…In the Nyquist plots, the curves of all the samples contained a semicircle at high frequency and a line at low frequency, representing the surface electron transfer processes and diffusion control sections, respectively. 37 The diameter of the semicircle was an indicator of the R ct value corresponding to the charge transfer kinetics. For the bare electrode (Pt plate and GCE), the fitted curves were like a line, implying that the R ct values were low, suitable for becoming electrode substrates.…”
Section: Results Of Xpsmentioning
confidence: 99%
“…14 Sharma consecutively electrodeposited polypyrrole and nickelphthalocyanine (NiPc) onto a bare Au-plate electrode (NiPc/pPy/Au) and conducted CV measurements to explore the electrochemical behavior of HD. 15 The results revealed that the NiPc/pPy/Au electrode exhibited excellent electrocatalytic activity and degradation ability. However, only one oxidation peak was observed in the CV plot and the oxidation process was not proposed.…”
mentioning
confidence: 93%